Design and Investigation of Linearly Polarized Modal Next-Generation Passive Optical Network–Free Space Optics System Considering Fiber-Wireless Link Losses - Meet Kumari; Satyendra K. Mishra (Photonics)
Next-generation passive optical networks (NG-PONs) are considered an essential solution for optical architectures, owing to the benefits of energy savings, service transparency, supporting several subscribers, and cost-effectiveness. In this work, a linearly polarized (LP [0,1]) modal bidirectional NG-PON using a graded-index multimode fiber (GIMMF) and free space optics (FSO) is realized. Four downlink/four uplink wavelengths are utilized under the impact of GIMMF nonlinearity, lens losses, and noise with a 100 m FSO link under clear air and weak turbulence. The results depict that a reliable 5.5 km range is obtained at an aggregate symmetric data rate of 40 Gbps. Also, the minimum focal length and lens reflectance of 0.085 m and 12–14.5% in the downlink as well as 0.08 m and 17–19% in the uplink are required, respectively, for a 10−9 bit error rate over a 5 km range. It is also realized that the generated LP modes offer an optimum power fraction of 0.52 to ~1 × 10−11 in the downlink and 0.53 to 1 × 10−10 in the uplink and phase values of 0.23 to 4.79 rad in the downlink and 0.96 to 5.81 rad in the uplink direction. Compared to other systems, the proposed design shows optimum performance and offers a −25.47 dB gain, a 28.84 dB noise figure, a −18.46 dBm output signal, and a 30.51 dB optical signal-to-noise ratio.